2020
DOI: 10.1002/wmh3.361
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and Morbid Obesity: Associations and Consequences for Policy and Practice

Abstract: While the impact of obesity on chronic disease has been widely examined, there has been less research regarding the influence of obesity on infectious diseases, particularly respiratory diseases. This exploratory research uses the currently available data on COVID‐19 cases and mortality, along with estimates of the morbidly obese populations in the United States by county, to examine the association between morbid obesity and deaths from COVID‐19 and to identify potential coincident spatial clusters of morbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Early reports in the pandemic of larger disparities in mortality relative to incidence suggested that the virus was deadlier for African Americans, exacerbating the inequalities produced by higher incidence rates ( Vasquez-Reyes, 2020 ). The higher rates of obesity and chronic diseases that have been linked to higher COVID-19 mortality suggest some reasons why case fatality may be elevated for African Americans and compound the risks from higher incidence rates ( Curtin et al., 2020 ; Jayawardena et al., 2020 ; Belanger et al., 2020 ; Tartof e al., 2020 ). While most studies have described higher COVID 19 mortality rates for African Americans, at least one recent report showed no difference in mortality related to COVID-19 between Blacks and other races/ethnicities among hospitalizations in a single health system ( Killerby et al., 2020 ; Gold et al., 2020 ; Ogedegbe et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early reports in the pandemic of larger disparities in mortality relative to incidence suggested that the virus was deadlier for African Americans, exacerbating the inequalities produced by higher incidence rates ( Vasquez-Reyes, 2020 ). The higher rates of obesity and chronic diseases that have been linked to higher COVID-19 mortality suggest some reasons why case fatality may be elevated for African Americans and compound the risks from higher incidence rates ( Curtin et al., 2020 ; Jayawardena et al., 2020 ; Belanger et al., 2020 ; Tartof e al., 2020 ). While most studies have described higher COVID 19 mortality rates for African Americans, at least one recent report showed no difference in mortality related to COVID-19 between Blacks and other races/ethnicities among hospitalizations in a single health system ( Killerby et al., 2020 ; Gold et al., 2020 ; Ogedegbe et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on risk factors associated with COVID-19 have considered the impact on mortality rates of a single risk factor such as obesity [7,8,9,10] or nutrition [11,12]. In a first gender-wise study, Nakeshbandi et al [13] showed with data collected from hospitalized patients over a month, that obesity is associated with higher mortality in men but not in women.…”
Section: Introductionmentioning
confidence: 99%
“…Initial ndings from early studies pointed towards age with older individuals being particularly at risk, those with non-communicable diseases (NCDs), such as, diabetes mellitus or cardiovascular diseases such as hypertension, respiratory conditions, and or kidney disease [4]. Further studies have led to the discovery that obesity is a plausible risk factor for severe illness, hospitalization and even death from COVID-19 [5,6].…”
Section: Introductionmentioning
confidence: 99%